2016
DOI: 10.1038/srep27500
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Hand, Foot and Mouth Disease and Its Potential Driving Factors in Hong Kong

Abstract: Hand-foot-and-mouth disease (HFMD) is a common childhood disease with substantial disease burden in Asia. Mixed results were reported on the associations between HFMD incidence and meteorological factors or school holidays, while limited studies focused on their association on transmissibility. We aimed to measure the transmissibility of HFMD and to examine its potential driving factors in Hong Kong. A likelihood-based procedure was used to estimate time-dependent effective reproduction number (Rt) based on we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 36 publications
5
16
2
Order By: Relevance
“…The range of R eff in previous studies was obviously disparate because of different experimental designs. Such as 1.14-1.24 by Yang et al [31], which was slightly lower than this study, it might be influenced by its focus that placed more emphasis on community. The range of R eff was between 2.5 to 5.5 from two studies in Hong Kong and Singapore [32,33], which was approximately consistent with this study.…”
Section: Assessment Of Transmissibility Of Hfmdcontrasting
confidence: 68%
“…The range of R eff in previous studies was obviously disparate because of different experimental designs. Such as 1.14-1.24 by Yang et al [31], which was slightly lower than this study, it might be influenced by its focus that placed more emphasis on community. The range of R eff was between 2.5 to 5.5 from two studies in Hong Kong and Singapore [32,33], which was approximately consistent with this study.…”
Section: Assessment Of Transmissibility Of Hfmdcontrasting
confidence: 68%
“…School terms did not significantly affect HFMD transmission rate. This is consistent with conclusions obtained from other studies for HFMD in Hong Kong and Singapore [39,40]: closing schools was found having a positive effect on reducing the spread of HFMD, but the impact was small. The average age of HFMD infection in China is around 3 years old, with a little younger age in provinces in the tropical and subtropical zones, and a little older in provinces in the north [2].…”
Section: Discussionsupporting
confidence: 92%
“…23,24 There is, however, a lack of empirical evidence on the effect of school closure on HFMD transmission: one exception is a review of HFMD in Hong Kong that revealed fewer HFMD consultations than expected during the 2003 severe acute respiratory syndrome and the 2009 influenza pandemic, which was attributed to various control measures including school closure. 25,26 This article aimed to assess the effect of school closure on HFMD transmission. In Singapore, HFMD is endemic with year-round transmission and is legally notifiable by physicians and childcare teachers, as well as actively screened for in preschool-aged children.…”
Section: Introductionmentioning
confidence: 99%